Employee commitment in Westrail - Firns, Ian; Travaglione, Antonio; Fink, Stephen (Graduate School of Business, Curtin University of Technology, 1995)
A study conducted in Westrail, the Western Australian Government Railways revealed that three underlying attitudes influenced the three dimensions of commitment (to organisation, work and co-worker) measured in a survey. Achievement of personal and career goals, propensity to stay with the organisation, trust in senior management and positive view of change were shown to be linked with the commitment dimensions and the underlying factors (affective, cognitive and behavioural commitment). Education, union membership, age and tenure were also found to be significantly correlated with aspects of commitment. Large downsizings have occurred at Westrail in recent years and commitment among workers is low, as is trust in senior management. The formal communications system needs attention and there is a general view that recent changes have not been for the positive benefit of the organisation. Linking personal goal achievement to Westrail employment may help to resolve the problem of low morale and commitment.